Effects of drought on enzyme activities and hotspot distribution along plant roots - Anh The, Luu; Van Dinh, Mai; Trung Quang, Do; Feizi, Ali; Duyen Thi Thu, Hoang (Vietnam Journal of Earth Sciences, 2023)
The frequency and severity of drought are projected to increase due to climate change, and Southeast Asia is no exception. Water scarcity hampers all biochemical processes in soil and induces stunted plant growth. While the rhizosphere harbors the most dynamic biochemical processes in the biosphere, the interaction mechanisms between residing microbes and plant roots under drought are poorly understood. In this research, soybean was planted in soil collected from the Red River Delta of Vietnam to test two hypotheses: (i) drought reduces rhizosphere enzyme activities and hampers the extent of the high enzyme activity along single root (from the root tips), and (ii) the turnover time of substrate by enzymes increases with decreasing soil moisture. The research aimed to characterize distributions of β-glucosidase and acid phosphatase enzymes in a distance from root tips. In addition, enzyme activities and plant root and shoot characteristics (length and weight) were investigated. The results demonstrated that shoot length was more impacted by drought than root length with the reduction of 25% for the former and 5% for the later. Meanwhile, the reduction in shoot weight was 61%, and root weight was 90% as the plant experienced drought conditions. The extent of a hotspot for enzymes along a single plant root, measured from the root tips, also decreased in response to drought. Furthermore, drought reduced both rhizosphere enzyme activities, resulting in a slower turnover time of β-D-glucopyranoside (MUF-G) and 4-methylumbelliferyl-phosphate(MUF-P) substrates. The research has shed light on the adverse impacts of drought on root-microbe interactions, which ultimately lead to poor crop growth.